PENGGUNAAN MEDIA BALOK KUBUS UNTUK MENINGKATKAN KEMAMPUAN MATEMATIK LOGIS ANAK USIA DINI DI TK NASYWA BANDUNG - Lina Oktariani Utami; Indah Sari Utami (IKIP Siliwangi, 2018)
This research originated from the problem of low logical mathematical abilities of children and Bandung. This is what underlies the formulation of the problem (1) What is the objective condition of the logical mathematical abilities of early childhood in group A TK Nasywa Bandung? (2) How does the implementation of early childhood logical mathematical ability learning through cubical blocks in group A TK Nasywa Bandung? (3) How to improve the logical mathematical abilities of early childhood after using cuboid beam media in group A Nasywa Bandung Kindergarten? The research objective was to obtain an overview of the use of cubic beam media to improve the logical mathematical abilities of early childhood in group A Nasywa Kindergarten Bandung. The method used in this research is classroom action research (CAR), which is carried out in three cycles using 12 research subjects. This study uses data collection techniques, observation and documentation. Preliminary observations of logical mathematical abilities with an assessment of Not Developing amounted to 73%, Started to Grow by 26% and Developed Very Good by 1%. However, after using cubical beam media, children's logical mathematical abilities show optimal abilities. Percentage of logical mathematical ability of children of assessment has not developed by 0%, started to develop by 25% and develops very well by 75%. Based on these data, recommendations given to child educators can be an alternative medium to improve the logical mathematical abilities of early childhood.